Adhatoda vasica (Nees.): A Review on its Botany, Traditional uses, Phytochemistry, Pharmacological Activities and Toxicity - Shamsuddin, Tahmida; Alam, Muhammad S.; Junaid, Md.; Akter, Rasheda; Hosen, S.M. Zahid; Ferdousy, Sakia; Mouri, Nusrat Jahan (Mini Reviews in Medicinal Chemistry, 2021)
Background: Adhatoda vasica (Nees.) of the family Acanthaceae has been used in the Southeast tropical zone as it is efficacious against headache, colds, cough, whooping cough, fever, asthma, dyspnea, phthisis, jaundice, chronic bronchitis, and diarrhea. It exhibits commendable pharmacological activities. Objective: The aim of the review is to provide a systematic overview of pharmacological activities with toxicity and clinical assessment, phytochemistry of A. vasica along with its characterization, geographical observation, phenology, traditional uses, as well as an organized representation of the findings. Method: The overall information of A. vasica was collected from various resources, including books, review papers, research papers, and reports which were obtained from an online search of globallyaccepted scientific databases. ChemDraw software was used to draw the compound’s structure. Results: Phytochemical review on A. vasica has led to the collection of 233 compounds of different types such as alkaloids, flavonoids, essential oils, terpenoids, fatty acids, phenols, etc. It is a promising source of potential phytopharmaceutical agent that exhibits diverse pharmacological activities, including antibacterial, antifungal, hepatoprotective, anti-ulcer, abortifacient, antiviral, antiinflammatory, thrombolytic, hypoglycemic, anti-tubercular, antioxidant, and antitussive activities. Conclusions: Sufficient number of studies on ethnopharmacology, traditional uses, and pharmacological activities of A. vasica are conducted. Furthermore, it is necessary to study the activity of chemical constituents for new drug design and discovery from natural products.
Keywords: traditional uses